M6A methyltransferase METTL3 promotes retinoblastoma progression via PI3K/AKT/mTOR pathway. Issue 21 (8th October 2020) - Zhang, Han; Zhang, Ping; Long, Chongde; Ma, Xinqi; Huang, Hao; Kuang, Xielan; Du, Han; Tang, Han; Ling, Xiangtian; Ning, Jie; Liu, Huijun; Deng, Xizhi; et al.
Abstract: Retinoblastoma (RB) is a common intraocular malignancy in children. Due to the poor prognosis of RB, it is crucial to search for efficient diagnostic and therapeutic strategies. Studies have shown that methyltransferase‐like 3 (METTL3), a major RNA N (6)‐adenosine methyltransferase, is closely related to the initiation and development of cancers. Nevertheless, whether METTL3 is associated with RB remains unexplored. Therefore, we investigated the function and mechanisms of METTL3 in the regulation of RB progression. We manipulated METTL3 expression in RB cells. Then, cell proliferation, apoptosis, migration and invasion were analysed. We also analysed the expression of PI3K/AKT/mTOR pathway members. Finally, we incorporated subcutaneous xenograft mouse models into our studies. The results showed that METTL3 is highly expressed in RB patients and RB cells. We found that METTL3 knockdown decreases cell proliferation, migration and invasion of RB cells, while METTL3 overexpression promotes RB progression in vitro and in vivo. Moreover, two downstream members of the PI3K/AKT/mTOR pathway, P70S6K and 4EBP1, were affected by METTL3. Our study revealed that METTL3 promotes the progression of RB through PI3K/AKT/mTOR pathways in vitro and in vivo. Targeting the METTL3/PI3K/AKT/mTOR signalling axis could be a promising therapeutic strategy for the treatment of RB.